Selected Effects of High-Pressure Grinding that Increase the Level of Ore Recovery - D. Saramak (International Mineral Processing Congress, 2018)
"High-pressure grinding technology is considered as one of the most efficient techniques of ore comminution, especially in terms of energy consumption. HPGR devices has been utilized in many mining-related industrial sectors, including iron and non-ferrous metal ores processing (copper, platinum, gold), as well as cement and limestone flour production. Even though the technology well known (introduced into mineral processing circuits in 80’s), there are still examples of ineffective operation of HPGR devices. This is a result of improper application of HPGR into individual crushing circuit. The purpose of the paper was to analyze selected effects achieved in HPGR on the course and effectiveness of beneficiation operations. Investigations were carried out for copper ore, and investigative programme was run for different values of HPGR pressing force, as well as changeable ore characteristics (content of fine size fractions, material moisture). All crushing products were then treated in flotation process, in order to determine useful mineral recovery. Results of investigations show that HPGR operating pressure influences the metal recovery in proportional way, however too extensive pressure values have relatively lower impact on increasing of the metal recovery. Particle size distribution of HPGR feed and its moisture have lower influence on recovery level than HPGR pressure, but too extensive moisture content influences the higher energy consumption of the roller press, together with less effective comminution. The second aspect raised in the paper was a possibility to control and optimize the HPGR-based circuit. There were presented the proposed approach to adjustment of HPGR operating parameters that enables the higher metal recovery.INTRODUCTION The high-pressure grinding technology, invented and developed by Professor Schoenert in 70’s (Schoenert, 1979), is currently regarded as one of the most efficient methods of hard ore comminution. Since then the technology was introduced into raw materials treatment circuits in many mining and mining-related industrial sectors, including iron and non-ferrous metal ores processing (copper, platinum, gold), as well as cement and limestone flour production. Considerable number of works concerning modeling and optimization of HPGR operation were also presented (Daniel & Morell, 2004, Tavares, 2005, Saramak, 2012, Saramak & Kleiv, 2013). Nowadays high-pressure grinding rolls devices are considered as well know technology with over 500 sold machines, according to various sources."